Diabetes, Metformin and the Clinical Course of Covid-19: Outcomes, Mechanisms and Suggestions on the Therapeutic Use of Metformin - Bailey, Clifford J.; Gwilt, Mike (Frontiers in Pharmacology, 2022)
Objectives: Pre-existing or new diabetes confers an adverse prognosis in people with Covid-19. We reviewed the clinical literature on clinical outcomes in metformin-treated subjects presenting with Covid-19. Methods: Structured PubMed search: metformin AND (covid [ti] OR covid-19 [ti] OR covid19 [ti] OR coronavirus [ti] OR SARS-Cov2 [ti], supplemented with another PubMed search: “diabetes AND (covid OR covid-19 OR covid19 OR coronavirus [ti] OR SARS-Cov2 [ti])” (limited to “Clinical Study”, “Clinical Trial”, “Controlled Clinical Trial”, “Meta-Analysis”, “Observational Study”, “Randomized Controlled Trial”, “Systematic Review”). Results: The effects of metformin on the clinical course of Covid-19 were evaluated in retrospective analyses: most noted improved clinical outcomes amongst type 2 diabetes patients treated with metformin at the time of hospitalisation with Covid-19 infection. These outcomes include reduced admission into intensive care and reduced mortality in subgroups with versus without metformin treatment. Conclusions: The pleiotropic actions of metformin associated with lower background cardiovascular risk may mediate some of these effects, for example reductions of insulin resistance, systemic inflammation and hypercoagulability. Modulation by metformin of the cell-surface ACE2 protein (a key binding target for SARS-CoV 2 spike protein) via the AMP kinase pathway may be involved. While pre-existing metformin treatment offers potentially beneficial effects and can be continued when Covid-19 infection is not severe, reports of increased acidosis and lactic acidosis in patients with more severe Covid-19 disease remind that metformin should be withdrawn in patients with hypoxaemia or acute renal disease. Prospective study of the clinical and metabolic effects of metformin in Covid-19 is warranted.